One‐stop microvascular screening service: an effective model for the early detection of diabetic peripheral neuropathy and the high‐risk foot. Issue 7 (10th May 2018) - Binns‐Hall, O.; Selvarajah, D.; Sanger, D.; Walker, J.; Scott, A.; Tesfaye, S.
Abstract: Aims: To evaluate the feasibility of a one‐stop microvascular screening service for the early diagnosis of diabetic distal symmetrical polyneuropathy, painful distal symmetrical polyneuropathy and the at‐risk diabetic foot. Methods: People with diabetes attending retinal screening in hospital and community settings had their feet examined by a podiatrist. Assessment included: Toronto Clinical Neuropathy Score evaluation; a 10‐g monofilament test; and two validated, objective and quick measures of neuropathy obtained using the point‐of‐care devices 'DPN‐Check', a hand‐held device that measures sural nerve conduction velocity and amplitude, and 'Sudoscan', a device that measures sudomotor function. The diagnostic utility of these devices was assessed against the Toronto Clinical Neuropathy Score as the 'gold standard'. Results: A total of 236 consecutive people attending the retinal screening service, 18.9% of whom had never previously had their feet examined, were evaluated. The prevalence of distal symmetrical polyneuropathy, assessed using the Toronto Clinical Neuropathy Score, was 30.9%, and was underestimated by 10‐g monofilament test (14.4%). The prevalence of distal symmetrical polyneuropathy using DPN‐check was 51.5% (84.3% sensitivity, 68.3% specificity), 38.2% using Sudoscan foot electrochemical skin conductance (77.4% sensitivity, 68.3% specificity), and 61.9% using abnormality in either of the results (93.2% sensitivity, 52.8% specificity). The results of both devices correlated with Toronto Clinical Neuropathy Score ( P <0.001). A new diagnosis of painful distal symmetrical polyneuropathy was made in 59 participants (25%), and 56.6% had moderate‐ or high‐risk foot. Participants rated the service very highly. Conclusions: Combined, eye, foot and renal screening is feasible, has a high uptake, reduces clinic visits, and identifies painful distal symmetrical polyneuropathy and the at‐risk foot. Combined large‐ and small‐nerve‐fibre assessment using non‐invasive, quantitative and quick point‐of‐care devices may be an effective model for the early diagnosis of distal symmetrical polyneuropathy. What's new?: A novel, one‐stop microvascular screening service in a hospital and community setting was initiated, whereby people with diabetes attending the annual eye screening, which has a high uptake, also underwent foot assessment aimed at detecting early peripheral neuropathy and the at‐risk foot requiring referral to the Foot Protection Team. Foot examination was carried out by a podiatrist. The service also identified previously undiagnosed painful neuropathy and had a high patient acceptability level. The service used novel, validated point‐of‐care devices for combined large‐ and small‐nerve‐fibre assessment, with the aim of diagnosing peripheral neuropathy early.